(untitled) (Current Horticulture, 2024)
The experiment was conducted to standardize container gardening techniques for fruit crops, guava (Psidium guajava L), pomegranate (Punica granatum L.) and citrus (Citrus aurantifolia L) to meeting out the nutritional requirement of city dwellers. There was maximum average plant biomass (1072 g/plant) in guava and minimum (423g) in pomegranate. Maximum shoot biomass (1012.11g) was recorded in plant grown in 45 cm x 45 cm and minimum (402.78g/plant) in 30x30 cm container. Destructive method was used to extract the root mass for analysis significant variation in root biomass was also recorded, maximum root biomass (506.11g) in guava and minimum (239.86 g) in pomegranate, however root biomass was recorded significantly maximum (509.78 g) in 45 cm x 45 cm. Root to shoot ratio was recorded maximum (0.63) in Citrus crops. The root:shoot ratio had significant correlation with stem girth and negatively correlated with fruit weight, fruit yield and root hairs diameter. Collar diameter has significantly positive correlation with plant height, fruit weight and yield. The container size as well as growing media (substrate) influenced the plant growth, root and shoot biomass, fruit yield and root morphology remarkably.